Application of nanoporous cobalt-based ZIF-67 metal-organic framework (MOF) for construction of an epoxy-composite coating with superior anti-corrosion properties. (January 2021) - Lashgari, Seyed Mohammad; Yari, Hossain; Mahdavian, Mohammad; Ramezanzadeh, Bahram; Bahlakeh, Ghasem; Ramezanzadeh, Mohammad
Highlights: A novel/nanoporous cobalt-based ZIF-67 functional MOF was construction. An intelligent anti-corrosion system based on Epoxy@ZIF-67-APS was fabricated. ZIF-67@APS NPs could diminish the steel corrosion by 81 % inhibition-degree. Epoxy coating filled with ZIF-67@APS NPs demonstrated excellent anti-corrosion properties. Abstract: In this study, for the first time, the ZIF-67 NPs were synthesized and used as a corrosion inhibitor container to enhance the barrier/active corrosion protection features of the epoxy coating. The protection performance of the ZIF-67 and ZIF-67@APS NPs filled epoxy composites was evaluated by EIS, salt-fog, and cathodic delamination experiments. The coating resistance values of the ZIF-67 and ZIF-67@APS NPs filled epoxy coatings reduced from 3.49 × 10 10 Ω. cm 2 to 2.47 × 10 9 Ω. cm 2 and from 8.16 × 10 10 Ω. cm 2 to 5.78 × 10 9 Ω. cm 2, respectively, after 50 days of immersion. The active corrosion inhibition effect of the epoxy/ZIF-67@APS NPs was demonstrated by electrochemical achievements.